Provisions for Payment and Dishonor of Securities in the Saudi Legal System: An Analytical and Critical Study in Light of the Balance Between Formalism and the Protection of the Lawful Holder’s Rights - Mohammad Saud Khasawneh (International Journal of Law Research and Studies, 2026)
This study aims to analyze the legal framework governing the payment of negotiable instruments under the Saudi Securities Law, and to assess its effectiveness in achieving a balance between protecting the lawful holder and ensuring the stability of commercial transactions. The study adopts an analytical and critical approach by examining the relevant statutory provisions, interpreting their application, and linking them to the economic function of negotiable instruments in the contemporary commercial environment. The research addresses the rules of payment in terms of its conditions, place, subject matter, and legal effects. It also examines the legal regime governing refusal of payment, including methods of proof, the scope of the drawee’s liability, and the legal consequences thereof, particularly the right of recourse available to the holder and other obligors. The findings indicate that the Saudi legislator has established a coherent legal framework that enhances confidence in negotiable instruments and provides effective protection for the holder by setting precise rules governing payment and reinforcing its binding nature. However, the study reveals a legislative tendency to prioritize formal requirements over functional and economic considerations, which may, in certain cases, undermine the efficiency of negotiable instruments as a swift means of payment. This is particularly evident in the continued reliance on traditional mechanisms such as protest procedures, limitations on modern methods of proof, and the relative complexity of recourse mechanisms. The study concludes that achieving the intended balance between protection and transactional stability requires a reconsideration of certain foundational aspects of the current framework. This includes adopting a more flexible approach to formal requirements, modernizing evidentiary methods, refining the scope of the drawee’s liability, and simplifying recourse procedures, in a manner that aligns with technological and banking developments and enhances the overall efficiency of the legal system governing negotiable instruments.